Allosteric and Biased G Protein-Coupled Receptor Signaling Regulation: Potentials for New Therapeutics - Khoury, Etienne; Clément, Stéphanie; Laporte, Stéphane A. (Frontiers in Endocrinology, 2014)
G protein-coupled receptors (GPCRs) are seven plasma membrane (PM)-spanning proteins that participate in many aspects of the endocrine function and are important targets for drug development. They transduce signals mainly, but not exclusively, via hetero-trimeric G proteins, leading to a diversity of intracellular signaling cascades. Ligands binding at the hormone orthosteric sites of receptors have been classified as agonists, antagonists and/or inverse agonists based on their ability to mainly modulate G protein signaling. Accumulating evidence also indicates that such ligands, alone or in combination with other ones such as those acting outside of the orthosteric hormone binding sites (e.g. allosteric modulators), have the ability to selectively engage subsets of signaling responses as compared to the natural endogenous ligands. Such modes of functioning have been variously referred to as “functional selectivity” or “ligand-biased signaling”. In this review, we provide an overview of the current knowledge regarding GPCR biased signaling and their functional regulation with a focus on the evolving concept that receptor domains can also be targeted to allosterically bias signaling, and discuss the usefulness of such modes of regulation for the design of more efficient therapeutics.